A new multipurpose soap dispenser prototype using design for manufacturing (DFM) approach - Mohamad Hafiz, Mohamad (2012)
Soap Dispenser is a personal care product which includes liquid soap and dispenser. This product generally use to washing a hand where can be found at the most toilet or restaurant. There has a lot of soap dispenser design and shape can be found in the market. The functions of the entire soap dispenser are almost same which is to dispense a liquid soap. The main objective of the project was to design and develop a multipurpose soap dispenser prototype. An additional function may be adapted to the current soap dispenser to enhance the ability of the soap dispenser in order to meet the current demand. The process of development may be conducted based on several tools of idea and concept generation such as New Product Development (NPD) and Design for Manufacturing (DFM). The development was focused on the additional functions and performance of the product. Another wish was to increase consistency and reliability of the prototyped product. An initial pre-study gave insight in how to come out with multipurpose functions that can be adapted into the soap dispenser. A wide variety of soap dispenser and the other hygiene care product were studied to obtain complete understanding. Next phase was to generate ideas and new concepts which after the product and concept evaluation resulted from the analysis. These concepts were made as functional mock-ups for further testing and evaluation and finally built as a fully prototype. A new multipurpose soap dispenser prototype finally produced by using Fortus 360mc prototype machine. The recommended additional functions from the customer’s survey for a new multipurpose soap dispenser prototype are mini dustbin and tissue compartment. The product can be assembled and functions as expected. Thus, objective of the project is achieved successfully.